Adsorption of Dyes From Aqueous Solution by Pummelo (Citrus grandis (L.) Osbeck) Peel - HU, C.W. (Asian Journal of Chemistry, 2010)
Laboratory investigations of the potential use of powdered pummelo peel as a sorbent for removal of the methylene blue, neutral red and congo red from aqueous solutions were conducted. The effects of various experimental parameters (e.g., initial pH, sorbent dose, initial dye concentration and contact time) were tested and optimal experimental conditions were ascertained. The isothermal data of methylene blue and neutral red fit the Langmuir model well and the processes of adsorption follow first order rate kinetics. As to the anionic dye congo red, the adsorption basically obeys Langmuir isotherm, but the uptake rate is rather lower than those of methylene blue and neutral red. The results in this study indicate that pummelo peel is a promising candidate for removing cationic dyes methylene blue and neutral red from the dye wastewater.